No increase in HIV or sexually transmissible infection testing following a social marketing campaign among men who have sex with men. Issue 5 (29th January 2009) - Guy, R; Goller, J; Leslie, D; Thorpe, R; Grierson, J; Batrouney, C; Kennedy, M; Lewis, J; Fairley, C; Ginige, S; Zablotska, I; Hellard, M
Abstract : Background: A social marketing campaign ran in 2004 in the Victoria to increase rates of HIV/sexually transmissible infection (STI) testing among men having sex with men (MSM). Methods: To evaluate the initiative data from HIV sentinel surveillance, laboratory data on testing for HIV/STIs and STI/HIV testing uptake reported in annual surveys were analysed. Results: The sentinel surveillance network showed no increase in the overall extent of HIV testing and no difference in the proportion of MSM reporting regular annual HIV testing during the campaign (43%) and post campaign (41%). The annual behavioural surveys showed that between 2004 and 2006 there was no significant increase in this overall proportion of MSM reporting having an HIV test in the last 12 months (p = 0.96). The behavioural surveys also showed an increasing trend in the proportion reporting specific STI tests over time: anal swab (26% to 39%, p⩽0.01) and urine test (42% to 50%, p⩽0.01) and there was a steady increase in the amount of STI testing at the clinics detected through the laboratory reports: chlamydia (average increment of 6.4 tests per month, p<0.01), gonorrhoea (6.5 tests per month, p⩽0.01) and syphilis (4.0 tests per month, p⩽0.01) but it began at least 2 years before the campaign and was not accelerated during the campaign. Conclusion: Based on a range of indicators there was no evidence that the campaign increased HIV/STI testing. These findings highlight the importance of evaluating public health campaigns to assess their impact to ensure that they are modified if no impact is identified.